2018
DOI: 10.4187/respcare.05918
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Recovery, Physical Activity Level, and Functional Status in Subjects With COPD

Abstract: Individuals with COPD who exhibit delayed 1-min heart rate recovery after the 6MWT exhibited worse exercise capacity as well as a more pronounced sedentary lifestyle and worse functional status than those without delayed heart rate recovery. Despite its assessment simplicity, heart rate recovery after the 6MWT can be further explored as a promising outcome in COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
0
21
1
Order By: Relevance
“…[2022] HRR is an indicator of autonomic nervous system function and parasympathetic activity level. [23,24] At the end of exercise, parasympathetic reactivation plays a leading role in heart rate regulation. Pierpont et al [25,26] showed that HRR is closely related to cardiovascular death and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[2022] HRR is an indicator of autonomic nervous system function and parasympathetic activity level. [23,24] At the end of exercise, parasympathetic reactivation plays a leading role in heart rate regulation. Pierpont et al [25,26] showed that HRR is closely related to cardiovascular death and all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
“… 21 A slowed response of the HR recovery at the end of the exercise corresponds to a reduced influence of the parasympathetic modulation on the sinoatrial node, representing higher probabilities of adverse cardiovascular outcomes. 20 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] The post-exercise heart rate (HR) recovery (off-kinetics) has been recognized as a predictor factor for exacerbation and mortality in multiple respiratory diseases (ie, COPD), and it is straightly related to functional capacity and quality of life. 20 Additionally, the HR off-transient reflects changes in cardiac autonomic modulation to manage the energy requirements during the post-exercise recovery, remarked by a gradual restoration of the parasympathetic activity. 21 A slowed response of the HR recovery at the end of the exercise corresponds to a reduced influence of the parasympathetic modulation on the sinoatrial node, representing higher probabilities of adverse cardiovascular outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations